2018
DOI: 10.1177/2151459318820222
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Elderly Patients With Atypical Femoral Fractures Compared to Typical Femoral Fractures for Length of Stay, Discharge Destination, and 30-Day Mortality Rate

Abstract: Introduction:Despite increasing recognition of atypical femoral fractures (AFFs), there’s conflicting evidence about incidence, aetiology, and short-term outcomes of these injuries. This study reports the incidence of AFFs at our center and compares the early postoperative outcomes against typical femoral fractures (TFFs).Methods:A retrospective observational cohort study of patients presenting to our trauma unit between November 2015 and July 2016 was undertaken. Inclusion criteria required radiologically con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
7
2
Order By: Relevance
“…This enabled rapid optimisation of fitness for surgery, early identification of rehabilitation goals and a return to pre-injury mobility and function. Our mean length of stay was 8.2 days, which is in contrast to 12.5 days, as reported by Davenport et al 20…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…This enabled rapid optimisation of fitness for surgery, early identification of rehabilitation goals and a return to pre-injury mobility and function. Our mean length of stay was 8.2 days, which is in contrast to 12.5 days, as reported by Davenport et al 20…”
Section: Discussioncontrasting
confidence: 45%
“…This enabled rapid optimisation of fitness for surgery, early identification of rehabilitation goals and a return to pre-injury mobility and function. Our mean length of stay was 8.2 days, which is in contrast to 12.5 days, as reported by Davenport et al 20 All patients had radiographs taken of their contralateral femurs to assess for bilateral disease. Four patients were found to have periosteal thickening and beaking of their lateral femoral cortices with the risk of impending fracture.…”
Section: Discussionmentioning
confidence: 49%
“…Although increased mortality associated with typical fragility fractures of the femur is known 10,11 , the rate of death associated with AFF has not been well established. A previous study in Sweden found lower mortality in AFF compared to ordinary fractures 12 , another study in an elderly population in UK found no difference in mortality at 30 days 13 . No previous studies in the South East Asian population have been performed.…”
Section: Accepted Articlementioning
confidence: 89%
“…A previous study in Sweden found lower mortality in patients with AFF in follow up duration of a mean of 4 years 12 . Another study found no differences in mortality in a 30 day follow up 29 . When we compared the mortality rates of patients with AFF and typical subtrochanteric femoral fractures to the national standardized age mortality rate in the population in chronological 5 year increment, we found that mortality risk for AFF patients were lower compared to the aged standardized mortality in the general population, however patients with typical fracture remains at a higher mortality risk compared to general population.…”
Section: Accepted Articlementioning
confidence: 90%
See 1 more Smart Citation